Differences in the cerebral hemodynamics regulation mechanisms of premature infants with intra-ventricular hemorrhage assessed by means of phase rectified signal averaging (2014)
Cerebral hemodynamics regulation consists of several mechanisms that try to keep brain homeostasis. In premature infants, due to the immaturity of their cerebral vascular bed, these mechanisms might be impaired exposing their brain to damage. The status of the cerebral regulation mechanism is classically assessed by measuring the coupling between some systemic variables, such as Mean arterial blood pressure (MABP) and concentration of blood gases, with surrogate measurements for cerebral blood flow, such as brain tissue oxygenation (rScO 2 ) measured by means of Near-infrared Spectroscopy. We hypothesized that the coupled dynamics between systemic variables and rScO 2 is different in premature infants that suffered from brain damage than in those with a favorable clinical outcome. Therefore, we explore the use of phase rectified signal averaging (PRSA) and bi-variate PRSA (BPRSA) in order to identify these differences. We found that the coupled dynamics between changes in MABP and cerebral oxygenation was different in premature infants that suffered III-IV grade intra-ventricular haemorrhage (IVH), when compared to control subjects.